Covid-19 Vaccines and its Adverse Events Following Immunization( AEFI) - Putri Dwi Bralianti; Femmy Nurul Akbar (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2021)
Background: The Indonesian government has begub to administer vaccines en mass and is planned in stages as an effort to prevent and control Covid-19 by immunity. To reduce the negative impact of immunization on individual health and the implementation of vaccination itself, it is best to know Covid-19 vaccines in Indonesia and their AEFI.Objective: The purpose of this article is to discuss Covid-19 vaccines in Indonesia and their AEFIMethod: Systematic review of studies about Covid-19 vaccines that have been and will be used in Indonesia along with an overview of AEFI.Results: There are five Covid-19 vaccines manufacturer that has been and will be used in Indonesia. The types of antigens used in the Covid-19 vaccine include a whole virus, protein subunits, and nucleic acid. Conclusion: Covid-19 vaccines are relatively safe and can rarely cause AEFI.